Technoparks as instruments of neoliberal governance :|the case of İTÜ ARIKENT - Eper, Ziya Batuhan. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2019., 2019)
Processes of neoliberalization in Turkey witness the gradual transformation of the character of university-industry partnerships. The enactment of Technology Development Zones Law in 2001 brought those relations in a whole new level where previously dispersed, irregular, informal practices of commercialization of knowledge and research were collected under a somewhat regulatory framework materialized in the form of technoparks. therefore, university campuses all around the country started to be occupied by various companies of commercial or academic origins. Moreover, various institutions of the state also found a new field of involvement with higher education. These new conditions not only intensified already complex relations between state institutions, academicians and companies but also further blurred the lines between positions of these actors. Within this novel context of neoliberal governance which is still in the making, this study scrutinizes the contradictions of this system through a case study on İTÜ ARIKENT that was conducted in 2010-2011. Contrary to the larger trend in the related literature which takes these spaces for granted as practical measurable solutions for catching up with the late train of modernity, this study took a critical stance. It employs the historical analysis of neoliberalism in Turkey coupled with the assemblage of various theoretical approaches to explain the positions and interactions of the actors involved. In that regard, ARIKENT was chosen to demonstrate the part of nu-merous historical and spatial dynamics from different scales coupled with the discussion of the circumstances of her various stakeholders that are entangled into each other in competitive and collaborative modalities.
Keywords: Research, Industrial -- Turkey -- Colleges.; Technological innovations -- Turkey.